Parody, Terror and the Making of Forms: Blake’s Aesthetics of the Sublime in The Book of Urizen - Ibata, Hélène (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2011)
In The Book of Urizen, Blake’s subversion of authoritative discourses includes a critique of Enlightenment aesthetics, and in particular a parody of the contemporary conception of the sublime. At the same time, however, the aesthetics of terror are displaced onto new grounds, as the artist draws attention to creative anxiety and the endless and laborious production process. This new emphasis, we show, is one of Blake’s most significant contributions to the debate on the sublime. As the self-reflexive dimension of The Book of Urizen attests, it is anchored in his own practice and in his awareness of the incommensurability of formal intentions and execution.